Study of the effect of crystal orientation on the mechanical response and fatigue life of solder joints under thermal cycling by crystal plasticity - Mingwei Xie; Gang Chen; Xiaoxia Yuan; Lei Zhang; Qiang Lin (Journal of Materials Research and Technology, 2023)
Electronic products are subjected to thermal cycling caused by power cycling in service processes. Owing to the difference in the coefficients of thermal expansion (CTEs) of solder joints and other packaging materials, solder joints suffer from thermomechanical fatigue, and cracks appear at their bonding interfaces. Solder joints are usually a single grain or three grains with Beachball morphology, and their composition is Sn-based Pb-free SAC305 (96.5Sn–3.0Ag–0.5Cu wt.%) solder, which exhibits obvious anisotropic mechanical behavior. This study investigated a thermal cycling simulation of Plastic Ball Grid Array (PBGA) packaging, in which the Anand model was used for solder joints, and the outermost solder joint was found to be a dangerous point. Sub-models were then established for this solder joint with several typical crystal orientations. The effect of crystal orientation under thermal cycling was simulated using thermomechanical crystal plasticity. When the c-axis of Sn crystal was perpendicular to the substrate, the deformation resistance was the largest, and the accumulation of equivalent plastic strain and strain energy dissipation was the slowest; hence, the fatigue life was the longest. As the angle between the c-axis and the substrate decreased, the deformation accumulated faster. When the c-axis was parallel to the substrate, the deformation of the solder joint was the fastest, and thus this joint was the first to fail and had the shortest fatigue life. In addition, the simulation of three grains indicated that orientations and their distributions had an influence on the shear strain accumulation of slip systems and fatigue life.